Intrinsic voltage gain and unit-gain frequency of omega-gate nanowire SOI MOSFETs - Perina, Welder F.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (My University, 2019)
This paper shows the influence of channel width (WNW) and channel length (L) on intrinsic voltage gain (AV) and on unit-gain frequency (ft) of omega-gate nanowire SOI MOSFET. The ft is calculated taking into consideration the experimental gate capacitance. The device showed excellent electrostatic control for the WNW of 10 nm, which improved transconductance, consequently, improving both AV and ft. This technology showed values of AV around 80 dB and a ft of over 200 GHz, proving that this device is an excellent for future analog applications like 5G communications and Internet-of-Things (IoT).
Keywords: Intrinsic Voltage Gain; Nanowire; Omega-gate; SOI; Unit-gain Frequency